Synthesis of uniform ordered mesoporous TiO2 microspheres with controllable phase junctions for efficient solar water splitting. Issue 6 (4th December 2018) - Zhang, Wei; He, Haili; Tian, Yong; Lan, Kun; Liu, Qi; Wang, Changyao; Liu, Yang; Elzatahry, Ahmed; Che, Renchao; Li, Wei; Zhao, Dongyuan
Abstract : Mesoporous TiO2 microspheres with controllable phase junctions have been synthesized by a facile coordination-mediated self-assembly method. Abstract : As a benchmark photocatalyst, commercial P25–TiO2 has been widely used for various photocatalytic applications. However, the low surface area and poorly porous structure greatly limit its performance. Herein, uniform ordered mesoporous TiO2 microspheres (denoted as Meso-TiO2 - X ; X represents the rutile percentage in the resultant microspheres) with controllable anatase/rutile phase junctions and radially oriented mesochannels are synthesized by a coordination-mediated self-assembly approach. The anatase/rutile ratio in the resultant microspheres can be facilely adjusted as desired (rutile percentage: 0–100) by changing the concentration of hydrochloric acid. As a typical one, the as-prepared Meso-TiO2 -25 microspheres have a similar anatase/rutile ratio to commercial P25. But the surface area (78.6 m 2 g −1 ) and pore volume (0.39 cm 3 g −1 ) of the resultant microspheres are larger than those of commercial P25. When used as the photocatalyst for H2 generation, the Meso-TiO2 -25 delivers high solar-driven H2 evolution rates under air mass 1.5 global (AM 1.5 G) and visible-light ( λ > 400 nm), respectively, which are significantly larger than those of commercial P25. This coordination-mediated self-assembly method paves a new way toward the design and synthesis of high performance mesoporous photocatalysts.